Nickel-based catalyst for MTO (methanol to olefin) byproduct oxide conversion as well as preparation method and application of nickel-based catalyst

By using nickel-based catalysts, the problem of low conversion of by-product oxides of MTO is solved, efficient aldehyde ketone conversion and high yield of alcohol compounds are achieved, wastewater discharge is reduced, and the yield of low-carbon olefins is improved.

CN119701959APending Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202311277895.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The direct refining conversion rate of MTO by-product oxides is low and cannot be effectively utilized, resulting in low yields of low carbon olefins and high wastewater discharge.

Method used

A nickel-based catalyst is used, which includes active metal components (such as nickel, zinc, iron, cobalt) and a modified support (zirconium modified silica), which is prepared by impregnation, precipitation, hydrothermal reaction and other steps, and is used for the hydrogenation reaction of MTO by-product oxides.

Benefits of technology

The aldehyde ketone conversion rate in MTO by-product oxides was significantly improved, and alcohol compounds with high selection and high yields were obtained, which reduced wastewater emissions and increased yields of low-carbon olefins.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nickel-based catalyst for MTO (methanol to olefin) byproduct oxide conversion as well as a preparation method and application of the nickel-based catalyst. The catalyst comprises an active metal component and a modified carrier, the active metal component comprises nickel or nickel and at least one of zinc, iron and cobalt; the modified carrier is a zirconium modified silicon dioxide carrier. The catalyst provided by the invention is used in the conversion reaction of the MTO by-product oxide, the ketoaldehyde conversion rate in the MTO by-product oxide is high, the alcohol selectivity is high, the recycling conversion rate of the MTO by-product oxide is greatly improved, low-carbon olefin with high additional value is obtained, and meanwhile, the wastewater discharge is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nickel-based catalyst for converting MTO by-product oxides, a preparation method and an application thereof. Background Art

[0002] Ethylene and propylene are important basic organic chemical raw materials, the cornerstone of the chemical industry, closely related to people's lives, and occupy an important position in the national economy. Traditional ethylene and propylene production mainly uses steam cracking, catalytic cracking and other processes using petroleum as raw materials. In recent years, MTO technology using coal-based methanol as raw material has developed rapidly. MTO refers to the technology of generating ethylene, propylene and other low-carbon olefins under the action of catalysts.

[0003] In the MTO process, aldehyde, ketone, alcohol and ether oxides are inevitably produced as by-products, which enter the water system to form oxide wastewater. Some of the concentrated oxides are directly returned to the MTO reactor for refining, among which the aldehyde and ketone conversion rate is low, and some are still treated as waste. In recent years, the treatment cost has become increasingly high. How to effectively utilize this part of oxides and reduce the carbon-based loss of raw materials has gradually become a difficult problem that needs to be solved in the oxide conversion process.

[0004] CN102325741A and CN102227393A disclose a method for producing olefins by direct reaction of ketone and hydrogen in the presence of a Cu-containing hydrogenation catalyst and a solid acid substance in a fixed bed reactor, with a reaction temperature of 50 to 300° C. The method does not record whether the raw material contains water.

[0005] CN111097499A, CN1962588A, CN102729861A, CN101927168A, CN11434548A and CN108126702A disclose methods for hydrogenating acetone using acetone as a raw material and a nickel-based or copper-based catalyst. The above methods use only acetone as a raw material and do not contain other ketones and aldehydes as by-product oxides of MTO, and do not consider the effects of other by-products such as water, ethers and aromatic hydrocarbons on the reaction. Summary of the invention

[0006] In order to solve the technical problems in the prior art such as low direct recycling conversion rate of MTO by-product oxides, inability to effectively utilize, and low yield of low-carbon olefins, the present invention provides a nickel-based catalyst for the conversion of MTO by-product oxides, as well as a preparation method and application. The catalyst provided by the present invention is used in the conversion reaction of MTO by-product oxides, and the ketone aldehyde conversion rate and alcohol yield in the MTO by-product oxides are high, which greatly improves the recycling conversion rate of MTO by-product oxides, obtains high value-added low-carbon olefins, and reduces the amount of wastewater discharged.

[0007] To solve the above problems, the present invention provides a nickel-based catalyst for the conversion of MTO by-product oxides in a first aspect, the catalyst comprising an active metal component and a modified carrier;

[0008] The active metal component includes nickel, or is selected from nickel and at least one of zinc, iron and cobalt;

[0009] The modified carrier is a zirconium-modified silica carrier.

[0010] Furthermore, in the nickel-based catalyst, based on the mass of the catalyst, the mass content of the modified carrier is 45% to 90%, the mass content of nickel as oxide is 4% to 40%, the mass content of zinc as oxide is 0 to 10%, the mass content of iron as oxide is 0 to 5%, and the mass content of cobalt as oxide is 0 to 3%.

[0011] Furthermore, in the nickel-based catalyst, the mass content of zinc in terms of oxide is 2% to 10% based on the mass of the catalyst.

[0012] Furthermore, in the nickel-based catalyst, the mass content of iron in terms of oxide is 1% to 5% based on the mass of the catalyst.

[0013] Furthermore, in the nickel-based catalyst, the mass content of cobalt in terms of oxide is 0.5% to 3% based on the mass of the catalyst.

[0014] Furthermore, based on the mass of the catalyst, the mass content of zirconium in the modified carrier is 0.2% to 10% in terms of oxide.

[0015] Furthermore, the specific surface area of ​​the modified carrier is 180 to 480 m 2 / g.

[0016] The second aspect of the present invention provides a method for preparing the above-mentioned nickel-based catalyst, comprising the following steps:

[0017] (1) preparing a zirconium-modified silica carrier;

[0018] (2) immersing the zirconium-modified silica support described in step (1) in an aqueous solution of an active metal component precursor, adding a precipitant and reacting to obtain a flocculated precipitated mixture;

[0019] (3) subjecting the flocculation precipitation mixture obtained in step (2) to a hydrothermal reaction, washing, drying and calcining to obtain the nickel-based catalyst.

[0020] Furthermore, the method for preparing the zirconium-modified silica carrier in step (1) is to mix the ammonium salt solution with the silica carrier, then add the zirconium salt solution, dry, and calcine to obtain the zirconium-modified silica carrier.

[0021] Furthermore, in step (1), the molar ratio of the silica carrier to the ammonium salt is 1 to 6:1, calculated as silica to ammonium ions; and the molar ratio of the silica carrier to the zirconium salt is 5 to 25:1, calculated as silica to zirconium.

[0022] Furthermore, the zirconium salt in step (1) is at least one of zirconium citrate, zirconium sulfate, zirconium nitrate, and zirconium chloride; the ammonium salt is at least one of ammonium carbonate, ammonium bicarbonate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium acetate, and ammonium nitrate. The pore volume of the silica carrier is 0.4-1.5 mL / g, and the specific surface area is 200-500 m 2 / g; preferably spherical, with a diameter of 0.5 to 5 mm.

[0023] Furthermore, the drying in step (1) can be carried out under conventional conditions in the art, preferably at 30 to 150° C. for 4 to 72 hours.

[0024] Furthermore, the calcination conditions in step (1) are: calcination at 200-500° C. for 4-12 hours.

[0025] Furthermore, in step (1), the molar concentration of the ammonium salt solution is 0.5 to 5 mol / L, and the molar concentration of the zirconium salt solution is 0.5 to 10 mol / L.

[0026] Furthermore, in step (2), the active metal component precursor is a soluble salt of the active metal, and the soluble salt of the active metal is selected from nickel salts, or at least one of nickel salts and zinc salts, iron salts and cobalt salts; the nickel salt is a soluble salt corresponding to the nickel element, preferably selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, nickel formate, nickel citrate, and basic nickel carbonate; the zinc salt is a soluble salt corresponding to the zinc element, preferably selected from at least one of zinc nitrate, zinc sulfate, zinc chloride, and zinc acetate; the iron salt is a soluble salt corresponding to the iron element, preferably selected from at least one of iron nitrate, iron sulfate, iron chloride, and iron acetate; the cobalt salt is a soluble salt corresponding to the cobalt element, preferably selected from at least one of cobalt nitrate, cobalt sulfate, cobalt chloride, and cobalt acetate.

[0027] Furthermore, the precipitant in step (2) is at least one of ammonia water, urea, sodium hydroxide, sodium carbonate and potassium carbonate.

[0028] Furthermore, in the aqueous solution of the active metal component precursor in step (2), the molar concentration of nickel salt is 1 mol / L to 5 mol / L, the molar concentration of zinc salt is 0 mol / L to 0.5 mol / L, the molar concentration of iron salt is 0 mol / L to 1 mol / L, and the molar concentration of cobalt salt is 0 mol / L to 1 mol / L.

[0029] Furthermore, the molar ratio of the modified silica carrier, nickel salt, zinc salt, iron salt and cobalt salt in step (2), calculated as SiO2, Ni, Zn, Fe, Co, is 10: (1-10): (0-0.5): (0-0.5): (0-1), preferably 10: (1-10): (0.01-0.5): (0.01-0.5): (0.01-1).

[0030] Furthermore, the impregnation method in step (2) adopts a supersaturated impregnation method, and the impregnation time is 12 to 24 hours.

[0031] Furthermore, the molar concentration of the precipitant in step (2) is 0.5 mol / L to 5 mol / L. The molar ratio of the nickel salt to the precipitant is 0.1 to 1:1.

[0032] Furthermore, the reaction temperature in step (2) is 40-60°C.

[0033] Furthermore, in step (2), the precipitant is added and the reaction is stirred, and the pH of the reaction needs to be controlled at 9-13.

[0034] Furthermore, the conditions of the hydrothermal reaction in step (3) are: reacting at 100-150° C. for 10-24 hours.

[0035] Furthermore, the washing, drying and calcining in step (3) are carried out by conventional methods in the art. Preferably, the calcination is carried out at 400-700° C. for 4-10 hours.

[0036] The third aspect of the present invention provides the use of the above nickel-based catalyst in the hydrogenation reaction of MTO by-product oxides.

[0037] Furthermore, the MTO by-product oxide raw material is contacted with the above-mentioned nickel-based catalyst and reacts with hydrogen to generate alcohol.

[0038] Furthermore, the mass content of water in the MTO by-product oxide raw material is 20% to 70%, preferably 50% to 70%; the mass content of polymethylbenzenes in the MTO by-product oxide raw material is 0 to 5%, wherein the polymethylbenzenes are one or more of toluene, ethylbenzene, trimethylbenzene, tetramethylbenzene, pentamethylbenzene, and hexamethylbenzene; the total mass content of oxides in the MTO by-product oxide raw material is 10% to 80%, wherein the oxides are a mixture of multiple selected from dimethyl ether, acetone, butanone, pentanone, hexanone, methanol, ethanol, propanol, isopropanol, acetaldehyde, propionaldehyde, and butyraldehyde, the mass content of ketone compounds in the oxides is 30% to 95%, and the mass content of aldehyde compounds is 5% to 20%.

[0039] Furthermore, the reaction temperature is 130-200°C, the gauge pressure is 0.2-1 MPa, and the mass space velocity of the oxide aqueous solution raw material is 0.3-1.0 h -1 , the volume ratio of hydrogen to oil is 4 to 10:1.

[0040] Furthermore, the nickel-based catalyst is activated before the MTO oxide hydrogenation reaction. The activation conditions are: in a reducing atmosphere, the temperature is 400-600°C, the pressure is 0.01-1 MPa, and the volume space velocity is 400-800 h -1 The reducing atmosphere is preferably a hydrogen atmosphere, wherein the volume content of hydrogen is 60% to 99%, preferably a hydrogen / nitrogen mixed atmosphere.

[0041] Furthermore, the alcohol generated by the reaction can be returned to the MTO reactor for further cracking to obtain light olefins.

[0042] In view of the problems of low direct recycling conversion rate of existing MTO by-product oxides, inability to effectively utilize, low yield of low-carbon olefins, etc., the nickel-based catalyst provided by the present invention is used for hydrogenation of aldehydes and ketones in MTO by-product oxides. The metal has a strong interaction with the modified carrier, and in the provided catalyst carrier, after modification, the acidic sites on the surface of the carrier are weakened, and the synergistic effect between the metal and silica is enhanced. Under the comprehensive effect, the catalyst overcomes the influence of impurities such as water, ethers and aromatic hydrocarbons in the MTO by-products on the reaction, significantly improves the conversion rate of aldehydes and ketones in the MTO by-product oxides, and obtains alcohol compounds with high selectivity and high yield. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.

[0044] In the context of this specification, the so-called specific surface area refers to the total area of ​​a sample per unit mass, including the internal surface area and the external surface area. Non-porous samples only have external surface area, such as silicate cement, some clay mineral powders, etc.; porous and porous samples have external surface area and internal surface area, such as asbestos fiber, diatomaceous earth and silica, etc. In the context of this specification, the so-called pore volume refers to the volume of pores per unit mass of porous materials. The so-called total pore volume refers to the volume of all pores per unit mass of silica (generally only pores with a pore diameter of less than 50 nanometers are counted). The pore structure parameters of silica, such as total pore volume and total specific surface area, are measured by a physical adsorption instrument (such as the TriStar3000 physical adsorption instrument of Mack Instruments, USA) to obtain the nitrogen physical adsorption and desorption isotherm, and then calculated by the BET method and t-plot method. The experimental conditions for the silica sample are: the measurement temperature is -169°C, and the silica is vacuum pretreated at 300°C for 10 hours before measurement.

[0045] [Example 1]

[0046] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of ammonium carbonate aqueous solution with an ammonium ion concentration of 1.4mol / L at room temperature, stirred for 5h, and then 10mL of zirconium oxychloride solution with a zirconium ion concentration of 2mol / L was gradually dropped in, and continued to stir for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 400℃ for 5h to obtain a zirconium-modified silica carrier (specific surface area of ​​369m 2 / g). The zirconium-modified silica carrier obtained above was immersed in 50mL of an aqueous solution of nickel nitrate with a nickel ion concentration of 0.9mol / L, iron nitrate with an iron ion concentration of 0.15mol / L, and cobalt nitrate with a cobalt ion concentration of 0.1mol / L at room temperature, immersed for 24h, heated to 50°C, stirred, and 3mol / L of sodium carbonate aqueous solution was gradually added thereto, and the pH was controlled to be 10.5 to obtain a flocculation precipitation mixture, and stirred for 30min, and then the obtained flocculation mixture was transferred to a hydrothermal kettle, placed in a constant temperature drying oven with a rotating hydrothermal kettle for hydrothermal reaction, the temperature was kept constant at 120°C for 12h, cooled, solid-liquid separated, washed, dried at 80°C for 10h, and calcined at 450°C for 6h to obtain a nickel-based catalyst, which was calculated as C1. The C1 catalyst obtained had a zirconium oxide content of 5%, a nickel oxide content of 10%, an iron oxide content of 4%, a cobalt oxide content of 2%, and a silica carrier content of 79% based on the mass of the catalyst.

[0047] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 500°C, pressure 0.1 MPa (gauge pressure), volume space velocity 600 h -1 , activation time 6h. After activation, the reaction temperature is lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) is introduced. The mixed MTO oxide solution is converted into a mixed gas through a preheater and enters a fixed bed reactor. The reaction temperature is 150°C, the reaction gauge pressure is 0.3MPa, the hydrogen volume oil ratio is 10:1, and the mass space velocity of the oxide aqueous solution raw material is 1h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0048] [Example 2]

[0049] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of ammonium dihydrogen phosphate aqueous solution with an ammonium ion concentration of 0.8mol / L at room temperature, stirred for 5h, and then 10mL of zirconium oxychloride solution with a zirconium ion concentration of 1.5mol / L was gradually dropped in, and continued to stir for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 400℃ for 5h to obtain a zirconium-modified silica carrier (specific surface area of ​​365m 2 / g). The zirconium-modified silica carrier obtained above was immersed in 50mL of an aqueous solution of nickel nitrate with a nickel ion concentration of 1.2mol / L, zinc nitrate with a zinc ion concentration of 0.1mol / L, and cobalt nitrate with a cobalt ion concentration of 0.12mol / L at room temperature, immersed for 24h, heated to 50°C, stirred, and gradually added with a 2mol / L sodium hydroxide aqueous solution, and the pH was controlled to be 11 to obtain a flocculation precipitation mixture, which was stirred for 30min, and then the obtained flocculation mixture was transferred to a hydrothermal kettle, placed in a constant temperature drying oven with a rotating hydrothermal kettle for hydrothermal reaction, the temperature was kept constant at 110°C for 12h, cooled, solid-liquid separated, washed, dried at 80°C for 10h, and roasted at 450°C for 6h to obtain a nickel-based catalyst, which was calculated as C2. The C2 catalyst obtained had a zirconium oxide content of 3%, a nickel oxide content of 15%, a zinc oxide content of 2%, a cobalt oxide content of 2.5%, and a silica content of 77.5% based on the mass of the catalyst.

[0050] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 450°C, pressure 0.15 MPa (gauge pressure), volume space velocity 500 h -1 , activation time 6h. After activation, the temperature was lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) was introduced. The mixed MTO oxide solution was converted into a mixed gas by a preheater and entered a fixed bed reactor. The reaction temperature was 160°C, the reaction gauge pressure was 0.2MPa, the hydrogen-to-oil volume ratio was 7:1, and the mass space velocity of the oxide aqueous solution raw material was 1.5h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0051] [Example 3]

[0052] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of ammonium acetate aqueous solution with an ammonium ion concentration of 1.2mol / L at room temperature, stirred for 5h, and then 10mL of zirconium oxychloride solution with a zirconium ion concentration of 1mol / L was gradually dropped in, and continued to stir for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 550℃ for 5h to obtain a zirconium-modified silica carrier (specific surface area of ​​366m 2 / g). The zirconium-modified silica carrier obtained above was immersed in 50mL of an aqueous solution of nickel nitrate with a nickel ion concentration of 0.7mol / L, iron nitrate with an iron ion concentration of 0.08mol / L, and cobalt nitrate with a cobalt ion concentration of 0.06mol / L at room temperature, immersed for 24h, heated to 60°C, stirred, and 1.5mol / L of urea aqueous solution was gradually added thereto, and the pH was controlled to be 12 to obtain a flocculation precipitation mixture, and stirred for 30min, and then the obtained flocculation mixture was transferred to a hydrothermal kettle, placed in a constant temperature drying oven with a rotating hydrothermal kettle for reaction, the temperature was kept constant at 130°C for 12h, cooled, solid-liquid separated, washed, dried at 80°C for 12h, and roasted at 550°C for 5h to obtain a nickel-based catalyst, which was calculated as C3. The C3 catalyst obtained had a zirconium oxide content of 2%, a nickel oxide content of 8%, an iron oxide content of 1.5%, a cobalt oxide content of 1%, and a silica content of 87.5% based on the mass of the catalyst.

[0053] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 550°C, pressure 0.25 MPa (gauge pressure), volume space velocity 500 h -1 , activation time 7h. After activation, the reaction temperature was lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) was introduced. The mixed MTO oxide solution was converted into a mixed gas through a preheater and entered a fixed bed reactor. The reaction temperature was 170°C, the reaction gauge pressure was 0.2MPa, the hydrogen-to-oil volume ratio was 8:1, and the mass space velocity of the oxide aqueous solution raw material was 0.5h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0054] [Example 4]

[0055] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of diammonium hydrogen phosphate aqueous solution with an ammonium ion concentration of 0.6mol / L at room temperature, stirred for 5h, and then 10mL of zirconium oxychloride solution with a zirconium ion concentration of 0.8mol / L was gradually dropped in, and continued to stir for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 500℃ for 6h to obtain a zirconium-modified silica carrier (specific surface area of ​​367m 2 / g). The zirconium-modified silica carrier obtained above was immersed in 50mL of an aqueous solution of nickel nitrate with a nickel ion concentration of 0.7mol / L, iron nitrate with an iron ion concentration of 0.08mol / L, and cobalt nitrate with a cobalt ion concentration of 0.06mol / L at room temperature, immersed for 24h, heated to 60°C, stirred, and 4mol / L of urea aqueous solution was gradually added thereto, and the pH was controlled to be 13 to obtain a flocculation precipitation mixture, and stirred for 30min, and then the obtained flocculation mixture was transferred to a hydrothermal kettle, placed in a constant temperature drying oven with a rotating hydrothermal kettle for hydrothermal reaction, the temperature was kept constant at 100°C for 12h, cooled, solid-liquid separated, washed, dried at 80°C for 12h, and calcined at 500°C for 7h to obtain a nickel-based catalyst, which was calculated as C4. The C4 catalyst obtained had a zirconium oxide content of 1%, a nickel oxide content of 12%, an iron oxide content of 1%, a cobalt oxide content of 1.5%, and a silica content of 84.5% based on the mass of the catalyst.

[0056] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 550°C, pressure 0.15 MPa (gauge pressure), volume space velocity 500 h -1 , activation time 7h. After activation, the temperature was lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) was introduced. The mixed MTO oxide solution was converted into a mixed gas by a preheater and entered a fixed bed reactor. The reaction temperature was 160°C, the reaction gauge pressure was 0.4MPa, the hydrogen volume oil ratio was 9:1, and the mass space velocity of the oxide aqueous solution raw material was 0.5h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0057] [Example 5]

[0058] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of diammonium hydrogen phosphate aqueous solution with an ammonium ion concentration of 1mol / L at room temperature, stirred for 5h, and then 10mL of zirconium oxychloride solution with a zirconium ion concentration of 1.2mol / L was gradually dropped in, and continued to stir for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 450℃ for 6h to obtain a zirconium-modified silica carrier (specific surface area of ​​365m 2 / g). The zirconium-modified silica carrier obtained above was immersed in 50mL of nickel nitrate aqueous solution with a nickel ion concentration of 2mol / L at room temperature for 24h, heated to 40°C, stirred, and gradually added with 4mol / L sodium carbonate aqueous solution, and the pH was controlled to be 10.5 to obtain a flocculation precipitation mixture, which was stirred for 30min, and then the obtained flocculation mixture was transferred to a hydrothermal kettle, and placed in a constant temperature drying oven with a rotating hydrothermal kettle for hydrothermal reaction at a constant temperature of 120°C for 12h, cooled, solid-liquid separated, washed, dried at 80°C for 12h, and calcined at 450°C for 6h to obtain a nickel-based catalyst, which was calculated as C5. The C5 catalyst obtained had a zirconium oxide content of 2.5%, a nickel oxide content of 20%, and a silica content of 77.5% based on the mass of the catalyst.

[0059] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 550°C, 0.15 MPa (gauge pressure), volume space velocity 500 h -1 , activation time 7h. After activation, the temperature was lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) was introduced. The mixed MTO oxide solution was converted into a mixed gas by a preheater and entered a fixed bed reactor. The reaction temperature was 160°C, the reaction gauge pressure was 0.4MPa, the hydrogen volume oil ratio was 9:1, and the mass space velocity of the oxide aqueous solution raw material was 0.5h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0060] [Comparative Example 1]

[0061] The catalyst was prepared according to Example 1, using a conventional silica carrier in the preparation process. The specific process is as follows:

[0062] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of nickel nitrate with a nickel ion concentration of 0.9mol / L, iron nitrate with an iron ion concentration of 0.15mol / L, and cobalt nitrate with a cobalt ion concentration of 0.1mol / L at room temperature, immersed for 24h, heated to 50°C, stirred, 3mol / L sodium carbonate aqueous solution was gradually added thereto, pH was controlled to be 10.5, a flocculation precipitation mixture was obtained, stirring was continued for 30min, and the obtained flocculation mixture was transferred to a hydrothermal kettle, placed in a constant temperature drying oven with a rotating hydrothermal kettle for hydrothermal reaction, the temperature was kept constant at 120°C for 12h, cooled, solid-liquid separated, washed, dried at 80°C for 10h, and roasted at 450°C for 6h to obtain a nickel-based catalyst, calculated as D1. The D1 catalyst obtained has a nickel oxide content of 10%, an iron oxide content of 4%, a cobalt oxide content of 2%, and a silica carrier content of 84% based on the catalyst mass.

[0063] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 500°C, pressure 0.1 MPa (gauge pressure), volume space velocity 600 h -1 , activation time 6h. After activation, the reaction temperature is lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) is introduced. The mixed MTO oxide solution is converted into a mixed gas through a preheater and enters a fixed bed reactor. The reaction temperature is 150°C, the reaction gauge pressure is 0.3MPa, the hydrogen volume oil ratio is 10:1, and the mass space velocity of the oxide aqueous solution raw material is 1h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0064] [Comparative Example 2]

[0065] The catalyst was prepared according to Example 1, and the silica carrier was not treated with ammonium salt during the preparation process. The specific process is as follows:

[0066] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 60mL zirconium oxychloride solution with a zirconium ion concentration of 2mol / L at room temperature, continued stirring for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 400℃ for 5h to obtain the treated modified silica carrier (specific surface area of ​​370m 2 / g). The treated modified silica carrier is immersed in 50mL of an aqueous solution of nickel nitrate with a nickel ion concentration of 0.9mol / L, iron nitrate with an iron ion concentration of 0.15mol / L, and cobalt nitrate with a cobalt ion concentration of 0.1mol / L at room temperature, immersed for 24h, heated to 50°C, stirred, and 3mol / L of sodium carbonate aqueous solution is gradually added thereto, and the pH is controlled to be 10.5 to obtain a flocculation precipitation mixture, and stirred for 30min, and then the obtained flocculation mixture is transferred to a hydrothermal kettle, and placed in a constant temperature drying oven with a rotating hydrothermal kettle for hydrothermal reaction, the temperature is kept constant at 120°C for 12h, cooled, solid-liquid separated, washed, dried at 80°C for 10h, and roasted at 450°C for 6h to obtain a nickel-based catalyst, which is calculated as D2. The D2 catalyst has a zirconium oxide content of 2%, a nickel oxide content of 10%, an iron oxide content of 4%, a cobalt oxide content of 2%, and a silicon dioxide content of 82% based on the catalyst mass.

[0067] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 500°C, pressure 0.1 MPa (gauge pressure), volume space velocity 600 h -1 , activation time 6h. After activation, the reaction temperature is lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) is introduced. The mixed MTO oxide solution is converted into a mixed gas through a preheater and enters a fixed bed reactor. The reaction temperature is 150°C, the apparent reaction pressure is 0.3MPa, the hydrogen-to-oil volume ratio is 10:1, and the mass space velocity of the oxide aqueous solution raw material is 1h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0068] [Comparative Example 3]

[0069] The catalyst was prepared according to Example 1, and no hydrothermal reaction treatment was used in the preparation process. The specific process is as follows:

[0070] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of ammonium carbonate aqueous solution with an ammonium ion concentration of 1.4mol / L at room temperature, stirred for 5h, and then 10mL of zirconium oxychloride solution with a zirconium ion concentration of 2mol / L was gradually dropped in, and continued to stir for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 400℃ for 5h to obtain a zirconium-modified silica carrier (specific surface area of ​​369m 2 / g). The zirconium-modified silica carrier obtained above was immersed in 50mL of an aqueous solution of nickel nitrate with a nickel ion concentration of 0.9mol / L, iron nitrate with an iron ion concentration of 0.15mol / L, and cobalt nitrate with a cobalt ion concentration of 0.1mol / L at room temperature, immersed for 24h, heated to 50°C, stirred, and 3mol / L of sodium carbonate aqueous solution was gradually added thereto, and the pH was controlled to be 10.5 to obtain a flocculation precipitation mixture, which was stirred for 30min, solid-liquid separation, washed, dried at 80°C for 10h, and calcined at 450°C for 6h to obtain a nickel-based catalyst, which was calculated as D3. The D3 catalyst obtained had a zirconium oxide content of 5%, a nickel oxide content of 10%, an iron oxide content of 4%, a cobalt oxide content of 2%, and a silica content of 79% based on the mass of the catalyst.

[0071] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 500°C, pressure 0.1 MPa (gauge pressure), volume space velocity 600 h -1 , activation time 6h. After activation, the reaction temperature is lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) is introduced. The mixed MTO oxide solution is converted into a mixed gas through a preheater and enters a fixed bed reactor. The reaction temperature is 150°C, the apparent reaction pressure is 0.3MPa, the hydrogen-to-oil volume ratio is 10:1, and the mass space velocity of the oxide aqueous solution raw material is 1h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0072] [Comparative Example 4]

[0073] The catalyst was prepared according to Example 1, and no precipitation reaction was used in the preparation process. The specific process is as follows:

[0074] Weigh 10 g of silica carrier (pore volume 1.08 mL / g, specific surface area 389 m 2 / g, spherical, equivalent diameter of 3mm), immersed in 50mL of ammonium carbonate aqueous solution with an ammonium ion concentration of 1.4mol / L at room temperature, stirred for 5h, and then 10mL of zirconium oxychloride solution with a zirconium ion concentration of 2mol / L was gradually dropped in, and continued to stir for 5h, then solid-liquid separation, dried at 80℃ for 8h, and calcined at 400℃ for 5h to obtain a zirconium-modified silica carrier (specific surface area of ​​369m 2 / g). The zirconium-modified silica carrier obtained above was immersed in 50mL of an aqueous solution of nickel nitrate with a nickel ion concentration of 0.9mol / L, iron nitrate with an iron ion concentration of 0.15mol / L, and cobalt nitrate with a cobalt ion concentration of 0.1mol / L at room temperature for 24 hours, and then the solid-liquid mixture was transferred to a hydrothermal kettle and placed in a constant temperature drying oven with a rotating hydrothermal kettle for hydrothermal reaction at a temperature of 120°C for 12 hours, cooled, solid-liquid separated, washed, dried at 80°C for 10 hours, and calcined at 450°C for 6 hours to obtain a nickel-based catalyst, which was calculated as D4. The D4 catalyst obtained had a zirconium oxide content of 5%, a nickel oxide content of 7%, an iron oxide content of 3%, a cobalt oxide content of 1%, and a silica content of 84% based on the catalyst mass.

[0075] The MTO oxide hydrogenation reaction was carried out in a fixed bed reactor. The catalyst loading was 5 g, and the catalyst was activated with a mixture of hydrogen and nitrogen before use, with a hydrogen volume content of 80%. The activation conditions were: temperature 500°C, pressure 0.1 MPa (gauge pressure), volume space velocity 600 h -1 , activation time 6h. After activation, the reaction temperature is lowered to the reaction temperature, and a mixed MTO oxide solution (water content of 57%, polymethylbenzene content of 3%, ketone oxide content of 30%, aldehyde oxide content of 10%) is introduced. The mixed MTO oxide solution is converted into a mixed gas through a preheater and enters a fixed bed reactor. The reaction temperature is 150°C, the apparent reaction pressure is 0.3MPa, the hydrogen-to-oil volume ratio is 10:1, and the mass space velocity of the oxide aqueous solution raw material is 1h -1 After the reaction was stable for 300 hours, samples were collected and analyzed. The reaction results are shown in Table 1.

[0076] Table 1 Catalytic performance results of various embodiments and comparative examples

[0077] catalyst Aldehyde conversion rate, % Ketone conversion rate, % Alcohol selectivity, % Example 1 C1 99.2 99.3 99.4 Example 2 C2 99.5 99.5 99.5 Example 3 C3 99.8 99.8 99.3 Example 4 C4 99.9 99.2 99.9 Example 5 C5 97.1 95.2 99.1 Comparative Example 1 D1 75.2 65.2 99.2 Comparative Example 2 D2 81.3 71.3 99.7 Comparative Example 3 D3 85.2 75.2 99.4 Comparative Example 4 D4 88.5 78.5 99.4

[0078] The embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A nickel-based catalyst for the conversion of MTO by-product oxides, the catalyst comprising an active metal component and a modified carrier; The active metal component includes nickel, or nickel and at least one of zinc, iron, and cobalt; The modified carrier is a zirconium-modified silica carrier.

2. The nickel-based catalyst according to claim 1, characterized in that In the nickel-based catalyst, based on the mass of the catalyst, the mass content of the modified carrier is 45% to 90%, the mass content of nickel calculated as oxide is 4% to 40%, the mass content of zinc calculated as oxide is 0 to 10%, the mass content of iron calculated as oxide is 0 to 5%, and the mass content of cobalt calculated as oxide is 0 to 3%.

3. The nickel-based catalyst according to claim 1, characterized in that Based on the mass of the catalyst, the mass content of zirconium in the modified carrier is 0.2% to 10.0% in terms of oxide.

4. The nickel-based catalyst according to claim 1, characterized in that The specific surface area of ​​the modified carrier is 180 to 480 m 2 / g.

5. A method for preparing the nickel-based catalyst according to any one of claims 1 to 4, comprising the following steps: (1) preparing a zirconium-modified silica carrier; (2) immersing the zirconium-modified silica support described in step (1) in an aqueous solution prepared with an active metal component precursor, adding a precipitant and reacting to obtain a flocculated precipitated mixture; (3) subjecting the flocculation precipitation mixture obtained in step (2) to a hydrothermal reaction, washing, drying and calcining to obtain the nickel-based catalyst.

6. The preparation method according to claim 5, characterized in that: The method for preparing the zirconium-modified silica carrier described in step (1) is to mix the ammonium salt solution with the silica carrier, then add the zirconium salt solution, dry, and calcine to obtain the zirconium-modified silica carrier.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the silica carrier to the ammonium salt in step (1) is 1 to 6:1, calculated on the basis of silica to ammonium ions; the molar ratio of the silica carrier to the zirconium salt is 5 to 25:1, calculated on the basis of silica to zirconium.

8. The preparation method according to claim 5, characterized in that: In step (2), the active metal component precursor is a soluble salt of the active metal, and the soluble salt of the active metal is selected from nickel salt, or at least one of nickel salt and zinc salt, iron salt and cobalt salt; wherein the molar ratio of the zirconium-modified silica, nickel salt, zinc salt, iron salt and cobalt salt in step (2) is 10:(1-10):(0-0.5):(0-0.5):(0-1) based on SiO2, Ni, Zn, Fe and Co, respectively.

9. Use of the nickel-based catalyst according to any one of claims 1 to 4 in hydrogenation reaction of by-product oxides of MTO.

10. The use according to claim 9, characterized in that: The reaction temperature is 130-200°C, the gauge pressure is 0.2-1.0 MPa, and the mass space velocity of the oxide aqueous solution raw material is 0.3-1.0 h -1 , the volume ratio of hydrogen to oil is 4 to 10:1.

Citation Information

Patent Citations

  • Nickel-based catalyst for preparing isopropyl alcohol by acetone hydrogenation and application thereof

    CN101927168A

  • Method for producing olefin

    CN102227393A

  • Process for production of olefins

    CN102325741A

  • An apparatus for continuous inclination adjustment of a pivotable vehicle part, in particular a pivotable vehicle armrest

    CN102729861A

  • Loaded nickel-based catalyst and preparation method and application thereof

    CN108126702A